The Accessibility as a Dimension of the Right to Education for Children and Adolescents in Situations of Human Mobility in Public Policy in Ecuador: Case 1497-20-JP - Ayala Quintana, Zeidy Maritza; Subía Cabrera, Andrea Carolina (Ius Humani. Jornal do direito, 2026)
This research analyzed the right to education for children and adolescents (NNA) in situations of human mobility in Ecuador, emphasizing the dimension of accessibility, primarily based on case No. 1497-20-JP of the Constitutional Court. Regarding the presented case, normative, administrative, and social barriers were identified that hinder access to education. The research adopted a qualitative approach, with a documentary and analytical design based on the study of regulations, jurisprudence, and public policies. The findings revealed that, despite regulatory advances, obstacles persist that limit the educational integration of NNA. The Constitutional Court established the obligation of the State to guarantee inclusive and corrective measures to eliminate discriminatory practices. It is concluded that it is necessary to strengthen the implementation of effective public policies that allow for equal opportunities in access to education.